The Rhetoric of Promoting Health - Hamilton, Margaret (Journal of Technical Writing and Communication, 2002)
This article uses Chaim Perelman's theories of argumentation to examine a recent Institute of Medicine (IOM) report, Promoting Health: Intervention Strategies from Social and Behavioral Research (2000). The IOM's text explores social and behavioral research to devise multipronged intervention strategies; it focuses on social, economic, behavioral, and political health as a means of assuring population health—and thereby expands the conventional boundaries of public health. Since Chaim Perelman's rhetoric is seldom applied in the field of health communication, employing his ideas to consider the role of style, arrangement, and argument in such a cutting-edge document can illuminate public health writing, as well as shed new light on Perelmanian rhetoric.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC9ocjV5LTVjNzEtZzd3dC1uMjZm